Analisis Pengaruh Mutu Pelayanan Kesehatan terhadap Kepuasan Pasien di Ruang Rawat Inap Renggali UPTD RSUD Datu Beru Takengon - Sri Hayati; Deli Theo; Asriwati Asriwati; Nur Aini; Juliandi Harahap (Pusat Riset dan Inovasi Nasional, 2024)
Hospitals are a comprehensive part of social and media organizations whose function is to provide complete health services to the community, both curative and rehabilitative, where hospital services extend to family and environmental services. The aim of the research is to find out and analyze the influence of health service quality on patient satisfaction in the inpatient room. UPTD Datu Beru Takengon Regional Hospital in 2023. The research design used in this research is an analytical survey with a cross sectional design. The population in this study was all 167 patients in the UPTD Inpatient Room at Datu Beru Takengon Regional Hospital. The number of samples that will be studied throughout the population is 62 people. Data analysis was carried out using univariate, bivariate and multivariate analysis. The statistical tests used are the chi square test and logistic regression. The results of the chi square test research show that there is an influence of 8 variables, namely technical competence, human relations, effectiveness, efficiency, continuity, security, human relations and comfort, which have a p-value <α 0.05, meaning that technical competence, human relations, effectiveness, efficiency, continuity, safety, human relations and comfort influence patient satisfaction in the UPTD inpatient room at Datu Beru Takengon Regional Hospital, and in the multivariate test there are 8 variables influencing technical competence, human relations, effectiveness, efficiency, continuity, security, interrelationships. human and comfort with the results of the multiple logistic regression test showing that the comfort variable is the most dominant with an odds ratio (OR) of 18.455, meaning that it influences patient satisfaction 18 times. The conclusion was that the dominant variable had the most influence on patient satisfaction in the UPTD Inpatient Room at Datu Beru Takengon Regional Hospital. It is recommended for hospitals to adopt policies to increase patient comfort in treatment rooms in order to produce optimal satisfaction for patients.